Flow and Microwave Induced Pellizzari Reactions: Synthesis of Heterocyclic Analogues of the Benzoxazepine Antipsychotic Agents Loxapine and JL-13. (4th December 2017) - Ranasinghe, Nadeesha; Mongeau, Enrico; Yuan, Gengyang; Minden, Zachary; Waldron, Scott; Patrick, Christopher; Fouad, Farid; Kappera, Sabiha; Jones, Graham B.
Abstract : An expeditious route to fused triazolo-pyrido benzoxazepines has been developed using flow and microwave-mediated cyclization chemistry. A range of substituted aryl hydrazides are coupled with a core chloroimine in good to excellent yield via a Pellizzari type process, producing 1, 2, 4-triazolo-pyrido [2, 3 - b ] [1, 5 ] benzoxazepines with structural similarity to known antipsychotic agents. Modifications allow for strategically functionalized derivatives, and installation of a fluoro group for use in PET imaging is also demonstrated. Given the affinity of the tricyclic core for 5-HT and dopamine receptors, the derivatives are expected to find utility in CNS research.